2020
DOI: 10.1177/1535370220938741
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular matrix in normal and pathological pregnancy: Future applications of microphysiological systems in reproductive medicine

Abstract: Remodeling of extracellular matrix in the womb facilitates the dramatic morphogenesis of maternal and placental tissues necessary to support fetal development. In addition to providing a scaffold to support tissue structure, extracellular matrix influences pregnancy outcomes by facilitating communication between cells and their microenvironment to regulate cellular adhesion, migration, and invasion. By reviewing the functions of extracellular matrix during key developmental milestones, including ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 168 publications
2
33
0
1
Order By: Relevance
“…Insu cient recovery of the myometrium can also affect placental growth. 23 Accordingly, in our study, the placental weight was lower when the interval between myomectomy and subsequent pregnancy was less than 2 years. This study also showed that the shorter the interval time between myomectomy and subsequent pregnancy, the higher the risk of emergency delivery.…”
Section: Discussionsupporting
confidence: 44%
“…Insu cient recovery of the myometrium can also affect placental growth. 23 Accordingly, in our study, the placental weight was lower when the interval between myomectomy and subsequent pregnancy was less than 2 years. This study also showed that the shorter the interval time between myomectomy and subsequent pregnancy, the higher the risk of emergency delivery.…”
Section: Discussionsupporting
confidence: 44%
“…The ECM is an integral and dynamic component of the endometrial microenvironment that mediates cellular and tissue-level function. 56 To engineer a fully synthetic ECM capable of supporting physiologically relevant culture of endometrial cells in vitro, we leveraged a multi- omic analysis of ex vivo human endometrial biopsies to characterize ECM composition and cell- ECM interactions. Specifically, we utilized single cell RNA sequencing (scRNAseq, N=6), and proteomic (LC-MS/MS, N=11) datasets from donors that represented the distinct phases across the menstrual cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular mechanisms underlying the spontaneous loss of a pregnancy are unknown (28). Decidualization plays a critical role in the implantation of the embryo through a regulatory network that coordinates trophoblast invasion of the maternal decidua-myometrium and remodeling of maternal uterine spiral arteries (29,30).…”
Section: Discussionmentioning
confidence: 99%